SALES MANAGEMENT LEVELS (Development Service Industry Management, 2024)
The article examines the essence of the term sales and provides the author's definition of it, which is specifically the action of selling goods or services, including all stages involved in the sale: from engaging with customers to reaching an agreement on the purchase of goods or services. It is indicated that the sales activity of the enterprise is implemented through sales channels, which are divided into direct (a distribution model in which the product manufacturer or service provider engages with the end user directly) and indirect (adistributionmodelthatinvolves an agents, like distributors, wholesalers, retailers or other intermediaries into the process of selling). Theenterprise'ssalesmanagementencompassesvariousaspectsandstrategiesthataredesignedtopromoteeffectivedevelopmentandensurethesuccessfulsaleofgoodsorservices. Thesales managementshouldbeunderstoodas theprocessoftransferringgoodsfromthemanufacturertotheconsumerundercertaincertainconditions. Salesmanagementiscarriedoutatthestrategic, tactical, andoperationallevelsandhascertaincharacteristics. In particular, atthestrategiclevel, planningandjustificationofthechoiceofoptimaldistributionchannelsforachievingthestrategicgoalsoftheenterpriseistakingplace. Marketingplansandstrategiesforadvertising, pricing, sales, andcustomerserviceareformedat a tacticallevel. Andattheoperationallevelthereiscoordinationofactivitiesandcontroloverdailysalesoperations, inventorymanagement, deliveryandwarehouseprocesses. Byallocatingtheselevels, itispossibletobuild a salessystemintheenterprisethattakesintoaccountthespecificitiesofsalesactivities.
Keywords: sales; sales activity; resources; sales management; distribution channel; direct distribution channel; indirect distribution channel